KAJIAN SOSIOLOGI PERAN MEDIA SOSIAL DALAM PENEGAKAN HUKUM DI INDONESIA - Waqingatul Hidayah, Yola (Negara dan Keadilan, 2018)
Along with the development of advances in technology and information, the existence of socialmedia has had positive and negative impacts on its users. In the modern era where everyone usessocial media, an unlawful act is likely to quickly go viral. Internet users can easily follow casedevelopments, provide support to victims and their families, or even gather support from netizensto oversee justice. Monitoring cases by internet users can put pressure on authorities to takeappropriate action to uphold justice. The function and role of social media in law enforcement inIndonesia is to act as social control, namely by providing criticism, correction, supervision andsuggestions, as well as encouraging the realization of the supremacy of the law, so that thepositive impact of this function is that law enforcers will be able to optimize the implementationof handling unlawful acts. in accordance with statutory regulations.